Do Carbon Emission Reporting and Carbon Trading Policies Improve Corporate Business Sustainability? - Setyawan, Setu; Juanda, Ahmad; Inata, Lia Candra (Universitas Negeri Semarang, 2025)
Purpose: The objective of this study is to examine and analyze the impact of carbon emission disclosure and carbon trading on improving corporate sustainability. Method: The data used in this study are secondary data obtained by documentation techniques. The sample in this study used 130 manufacturing companies in 2023. The data analysis technique in this study used IBM SPSS Statistics 26 software with stages including descriptive statistics, classical assumption tests, multiple linear regression analysis. Findings: The results of the study show that carbon emission disclosure has a positive effect on business sustainability. While carbon trading policies do not affect business sustainability. Carbon trading policies have not been widely implemented by companies in Indonesia, because companies in Indonesia are still in the process of preparing to implement carbon trading policies. Novelty: Research in Indonesia on the impact of carbon emission disclosure and carbon trading leading to business sustainability is still rarely conducted, researchers focus on company performance and bridge the issues related to environmental damage caused by manufacturing companies, efforts that can be made by manufacturing companies. Therefore, it is necessary to conduct research on the impact of carbon emission disclosure and carbon emission trading policies on business sustainability.